Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Rechnungslegung nach IFRS und HGB: Lehrbuch zur Theorie und Praxis der Unternehmenspublizität mit Beispielen und Übungen - Ruhnke, Klaus; Simons, Dirk; Sievers, Sönke

Asymmetric, non-uniform 3-dB directional coupler with 300-nm bandwidth and a small footprint - Nikbakht, Hamed; Khoshmehr, Mohammad Talebi; van Someren, Bob; Teichrib, Dieter; Hammer, Manfred; Förstner, Jens; Akca, B. Imran (Optics Letters)
Here we demonstrate a new, to the best of our knowledge, type of 3-dB coupler that has an ultra-broadband operational range from 1300 to 1600 nm with low fabrication sensitivity. The overall device size is 800 µm including in/out S-bend waveguides. The coupler is an asymmetric non-uniform directional coupler that consists of two tapered waveguides. One of the coupler arms is shifted by 100 µm in the propagation direction, which results in a more wavelength-insensitive 3-dB response compared to a standard (not shifted) coupler. Moreover, compared to a long adiabatic coupler, we achieved a similar wavelength response at a 16-times-smaller device length. The couplers were fabricated using the silicon nitride platform of Lionix International. We also experimentally demonstrated an optical switch that is made by using two of these couplers in a Mach–Zehnder interferometer configuration. According to experimental results, this optical switch exhibits –10 dB of extinction ratio over the 1500–1600 nm wavelength range. Our results indicate that this new type of coupler holds great promise for various applications, including optical imaging, telecommunications, and reconfigurable photonic processors where compact, fabrication-tolerant, and wavelength-insensitive couplers are essential.
Keywords: tet_topic_waveguide

Separation Of Multi-Component Parts For Mechanical Recycling – Study About Basic Approaches Using A Heating Process - Hopp, Matthias; Schäffer, Leon

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Mit der richtigen Auslegung zur sicheren Verbindung - Moritzer, Elmar; Held, Christian; Hopmann, C.; Kramer, M. (Kunststoffe)

Wie bewährt sich das duale berufliche Ausbildungssystem der industriellen Metall und Elektroausbildung unter Pandemiebedingungen? Lehrkräfte und Auszubildende reflektieren - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s): Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)

Reproducibility and Scattering in Additive Manufacturing: Results from a Round Robin on PBF-LB/M AlSi10Mg Alloy - Schneider, M.; Bettge, D.; Binder, M.; Dollmeier, K.; Dreyer, Malte; Hilgenberg, K.; Klöden, B.; Schlingmann, T.; Schmidt, J. (Practical Metallography)
Abstract The round robin test investigated the reliability users can expect for AlSi10Mg additive manufactured specimens by laser powder bed fusion through examining powder quality, process parameter, microstructure defects, strength and fatigue. Besides for one outlier, expected static material properties could be found. Optical microstructure inspection was beneficial to determine true porosity and porosity types to explain the occurring scatter in properties. Fractographic analyses reveal that the fatigue crack propagation starts at the rough as-built surface for all specimens. Statistical analysis of the scatter in fatigue using statistical derived safety factors concludes that at a stress of 36.87 MPa the fatigue limit of 10 7 cycles could be reached for all specimen with a survival probability of 99.999 %.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Event-Driven Programming of FPGA-accelerated ROS 2 Robotics Applications - Lienen, Christian; Platzner, Marco (2022 25th Euromicro Conference on Digital System Design (DSD))

Ruelle–Pollicott resonances for manifolds with hyperbolic cusps - Guedes Bonthonneau, Yannick; Weich, Tobias (Journal of the European Mathematical Society)
Keywords: Applied Mathematics; General Mathematics

Soziotechnische Herausforderungen bei der Einführung von RPA managen - Hobscheidt, Daniela; Menzefricke, Jörn Steffen; Gabriel, Stefan; Kühn, Arno; Dumitrescu, Roman (Praxishandbuch Robotic Process Automation (RPA))

The adrenal steroid profile in adolescent depression: a valuable bio-readout? - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hauffa, Berthold P.; Hebebrand, Johannes; Grasemann, Corinna (Translational Psychiatry)
Abstract There is preliminary evidence that adrenal steroids other than cortisol may be valuable biomarkers for major depressive disorder (MDD). So far, studies have been conducted in adults only, and conclusions are limited, mainly due to small sample sizes. Therefore, the present study assessed whether adrenal steroids serve as biomarkers for adolescent MDD. In 261 depressed adolescents (170 females) treated at a single psychiatric hospital, serum adrenal steroids (progesterone, 17-hydroxyprogesterone, 21-deoxycortisol, 11-deoxycortisol, cortisol, cortisone, deoxycorticosterone, corticosterone) were determined by liquid chromatography-tandem mass spectrometry. Findings were compared to that of an age- and sex-matched reference cohort ( N = 255) by nonparametric analysis of variance. Nonparametric receiver operating characteristics (ROC) analyses were conducted to evaluate the diagnostic performance of single steroids and steroid ratios to classify depression status. Sensitivity analyses considered important confounders of adrenal functioning, and ROC results were verified by cross-validation. Compared to the reference cohort, levels of deoxycorticosterone and 21-deoxycortisol were decreased ( P < 0.001). All other glucocorticoid- and mineralocorticoid-related steroids were increased ( P < 0.001). The corticosterone to deoxycorticosterone ratio evidenced excellent classification characteristics, especially in females (AUC: 0.957; sensitivity: 0.902; specificity: 0.891). The adrenal steroid metabolome qualifies as a bio-readout reflecting adolescent MDD by a distinct steroid pattern that indicates dysfunction of the hypothalamus–pituitary–adrenal axis. Moreover, the corticosterone to deoxycorticosterone ratio may prospectively qualify to contribute to precision medicine in psychiatry by identifying those patients who might benefit from antiglucocorticoid treatment or those at risk for recurrence when adrenal dysfunction has not resolved.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Inwiefern ist die Professionalisierung in Praxisphasen schulformspezifisch? - Caruso, Carina; Seifert, Andreas (Österreichische Religionspädagogische Forum)
Im Zentrum dieses Beitrags stehen Ergebnisse der Messung pädagogischer Kompetenzen Studierender der Theologie, die das Praxissemester in Deutschland absolviert haben. Das bildungswissenschaftliche Wissen, Kompetenzselbsteinschätzungen und ihre Entwicklung sowie die Einschätzung der im Praxissemester erreichten Ziele Studierender werden dabei unter Berücksichtigung der Ausrichtung des Lehramtsstudiums auf eine Schulform betrachtet. Um die Ergebnisse der Messung bildungswissenschaftlichen Wissens und die der Messung von Kompetenzselbsteinschätzungen zu kontextualisieren (N = 304), wird zuerst die Relevanz des (bildungswissenschaftlichen) Wissens als Ausgangspunkt des Könnens herausgearbeitet. Daran anschließend werden Befunde zur schulformspezifischen Professionalisierung resümiert. Anschließend werden Hypothesen hergeleitet, die Anlage der Studie sowie die Testinstrumente vorge- stellt, die Ergebnisse präsentiert und diskutiert. Die Ergebnisse zeigen wider Erwarten, dass sich weder das bildungswissenschaftliche Wissen, die Kompetenzselbsteinschätzungen und ihre Entwicklung noch die Einschätzung der im Praxissemester erreichten Ziele angehender Lehrkräfte in Abhängigkeit der Schulformen unterscheiden. Die Diskussion bezieht sich u.a. auf die Struktur der Lehramtsstudiengänge, die Denkfiguren zur Entwicklung von Können und die Konzeption der Messinstrumente.
Keywords: Bildungswissenschaftliches Wissen; Kompetenzmessung; Kompetenzselbsteinschätzung; Praxissemester; Professionalisierung / competence measurement; competence self-assessment; educational knowledge; internship; professionalization

Das Belastungserleben von Lehramtsanwärterinnen und -anwärtern im Vorbereitungsdienst - Bruns, Marike; Caruso, Carina; Ackermann, Luisa (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Die Ausbildung von Lehrkräften teilt sich in Studium und Vorbereitungsdienst. Während im Studium Wissen grundgelegt wird, dient der Vorbereitungsdienst, der überwiegend in der Schule stattfindet, dem Erwerb praktischer Kompetenzen, was den Rückbezug auf theoretisch fundierte Kenntnisse und den Aufbau erfahrungsbasierten Wissens umfasst. Die Maßnahmen zur Eindämmung der Corona-Pandemie verändern nicht nur den Schulalltag, sondern haben auch Einfluss auf die Kompetenzentwicklung angehender Lehrkräfte im Vorbereitungsdienst, die ihre Berufsausbildung unter veränderten Rahmenbedingungen durchführen müssen. Die aktuellen Rahmenbedingungen können u. a. aufgrund fehlender bzw. eingeschränkter Praxiserfahrungen eine reguläre Ausbildung erschweren, was zu einem erhöhten Belastungsempfinden der angehenden Lehrkräfte beitragen kann. In diesem Beitrag wird Bezug genommen auf Daten einer explorativen Interviewstudie mit Lehramtsanwärterinnen und -anwärtern aus Nordrhein-Westfalen (N = 19), die während der Pandemie im Jahr 2020 ihren Vorbereitungsdienst absolviert haben. Es wird dabei den Fragen nachgegangen, welche Belastungsfaktoren im Zusammenhang mit der Corona-Pandemie während des Vorbereitungsdienstes auftreten können und inwieweit sich angehende Lehrkräfte während ihres Vorbereitungsdienstes vor dem Hintergrund der aktuellen Rahmenbedingungen infolge der Corona-Pandemie als belastet erleben.
Keywords: Corona-Pandemie; Lehramtsanwärter:innen; Lehrer:innenausbildung; Professionalisierung; Vorbereitungsdienst / corona pandemic; prospective teachers; teacher training; professionalization; preparatory service

Von der Not zur Tugend!? - Caruso, Carina; Bruns, Marike; Harteis, Christian (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s) Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Der Begriff der „Zwangsdigitalisierung“ beschreibt, dass als eine Folge der Corona-Pandemie Präsenzformate durch digital gestützte Settings ersetzt werden sowie Alter- nativen zur Kommunikation und für das gemeinsame Arbeiten und Lernen in Präsenz gefunden werden mussten. Digital gestützte Lehr-Lernsettings scheinen seit dem ersten Lockdown sowohl an Schulen als auch an Hochschulen eine Möglichkeit dafür darzustellen, die Lern- und Entwicklungsprozesse (z. B. von Schülerinnen und Schülern, angehenden Lehrkräften) trotz physischer Distanz weiterzuführen. In diesem Beitrag werden die mit der Zwangsdigitalisierung an den Hochschulen verbundenen Chancen und Grenzen für die Entwicklung digitalisierungsbezogener Kompetenzen angehender Lehrkräfte herausgearbeitet. Dabei richtet sich der Blick auf den Wert von Erfahrungen für Lernen und Entwicklung. Zudem wird, gemäß der den Angebots-Nutzungs-Modellen inhärenten Logik einer „Wirkkette“, Bezug genommen auf Perspektiven von Studierenden, deren prospektiven Schülerinnen und Schülern sowie von Dozierenden.
Keywords: Hochschullehre; Lehrer:innenausbildung; Medienkompetenz / teacher education; teaching at university; media literacy

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for researching professional learning and development: Challenges, applications and empirical illustrations)
Q is an exploratory method used to elicit discrete patterns of subjectivity (e.g., subjective theories, beliefs). To be more concrete, Q method aims to identify homogeneous latent clusters of viewpoints towards a certain topic from a larger more heterogeneous set of (a priori unknown) different viewpoints held by respondents in the population. For this purpose, study participants are asked to sort qualitative statements concerning a certain topic (e.g., their beliefs toward something) into a grid roughly following a normal distribution indicating whether they agree or disagree with the given propositions. This results in a so-called Q-sort for each participant that then can be fed into a factor analysis that compares the different Q-sorts and groups them by similarity. In the first part of the chapter, Q method is introduced. The second part of the chapter describes a small study focusing on student teachers and their perspectives concerning upcoming long-term school internships.
Keywords: Q method; Subjectivity; Internships; Teacher education; Q sort